BET proteins: Investigating BRDT as a potential target for male contraception. Issue 6 (15th March 2020) - Wisniewski, Andrea; Georg, Gunda I.
Graphical abstract: Abstract: While many contraception options are available for women, birth control methods for men are limited to condoms and vasectomy. Past research into male contraceptives has focused on hormonal options but the associated side effects have thus far precluded this method from reaching the market. Non-hormonal male contraceptives and vas occlusion have also been explored, but to date no method has progressed past clinical testing. Recent interest in epigenetic research has unveiled a new potential non-hormonal male contraceptive target: the testis-specific bromodomain BRDT. Potent inhibitors for bromodomain-containing proteins are described in the literature, but a BRDT-specific compound has yet to be designed, prepared and tested. The high similarity between bromodomain proteins of the BET family makes development of selective and specific inhibitors both difficult and necessary. Selective inhibition of BRDT by a small molecule is an exciting new target in the search for a new non-hormonal male contraceptive.